2018
DOI: 10.21034/sr.567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Government Guarantees and the Valuation of American Banks

Abstract: Banks' ratio of the market value to book value of their equity was close to 1 until the 1990s, then more than doubled during the 1996-2007 period, and fell again to values close to 1 after the 2008 financial crisis. Sarin and Summers (2016) and Chousakos and Gorton (2017) argue that the drop in banks' market-to-book ratio since the crisis is due to a loss in bank franchise value or profitability. In this paper we argue that banks' market-to-book ratio is the sum of two components: franchise value and the value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…33 The former falls short of the observed change -0.33% in the model versus 0.58% in the data. The fact that financial credit spreads have remained persistently high since the financial crisis has also been noted by Atkeson et al (2018): our analysis shows that belief revisions in response to the observed shocks during 2008-'09 can help explain a significant portion of this increase. 34 Spreads for non-financial firms are predicted to rise by less than that of financials.…”
Section: Datâ G 2007ĝ2014supporting
confidence: 65%
See 1 more Smart Citation
“…33 The former falls short of the observed change -0.33% in the model versus 0.58% in the data. The fact that financial credit spreads have remained persistently high since the financial crisis has also been noted by Atkeson et al (2018): our analysis shows that belief revisions in response to the observed shocks during 2008-'09 can help explain a significant portion of this increase. 34 Spreads for non-financial firms are predicted to rise by less than that of financials.…”
Section: Datâ G 2007ĝ2014supporting
confidence: 65%
“…This implicitly assumes that intermediary leverage is not too high relative to the shocks on the asset portfolio, which is not a bad approximation given our calibration of corporate default rates. While it is possible to relax this assumption and allow for default on intermediary debt even in the absence of the financial shock, Atkeson et al (2018) and Sarin and Summers (2016) argue that the post-crisis changes in bank leverage have not really led to lower risk premia. Our specification is consistent with this finding.…”
Section: B2 Intermediationmentioning
confidence: 99%
“…This implicitly assumes that intermediary leverage is not too high relative to the shocks on the asset portfolio, which is not a bad approximation given our calibration of corporate default rates. While it is possible to relax this assumption and allow for default on intermediary debt even in the absence of the financial shock,Atkeson et al (2018) andSarin and Summers (2016) argue that the post-crisis changes in bank leverage have not really led to lower risk premia. Our specification is consistent with this finding.47 To see this, suppose an intermediary offers a contract where she receives a positive payment in the no-default state.…”
mentioning
confidence: 99%
“…) is the ex-post equity capital of the bank inspected by the regulator. If inspected, the situation can be divided into two cases, as shown in (6). If the bank satisfies the capital requirement (Φ t ≥ φ), its ex-post equity capital is the same as E N (L t ,n t ; z t+1 ).…”
Section: Dynamic Model With Heterogeneous Banksmentioning
confidence: 99%
“…stricter capital regulation causes financial institutions to increase measures of regulatory capital. However, such increase in regulatory capital is offset by a decline in the franchise value of the financial institutions, and thus, the banking system becomes fragile, that is, "measures of regulatory capital are flawed" (see also Atkeson et al (2018), Begenau et al…”
mentioning
confidence: 99%